Elaboración de la guía metodológica de gerencia de proyectos en las áreas de integración, alcance, tiempo y costo : caso práctico: construcción del conjunto residencial de vivienda de interés social “Parque Real” en el municipio de Mosquera Cundinamarca (2015)
At the beginning of this project it was detected that in "La Constructora" it is necessary to minimize the deviations in time and cost in the construction stage of real estate projects of social interest housing. Based on a diagnosis of the current state of project management of "La Constructora", this shows that the construction company uses processes in the area of ​​project management, but does not have the procedures or formats necessary to develop an organized management and complet. The present project seeks to develop a methodological guide of project management for the areas of integration, scope, time and cost, applied to the social real estate project real park that seeks to contribute to the improvement of project management, which the construction company currently has . The design of the guide is based on the integral management system of the construction company and procedures are developed according to the parameters established by it. For each of the procedures, the step-by-step description is made of each of the activities to be carried out, the documents that must be generated and who is the responsible person in each of the stages. The necessary formats to develop the methodological guide are also established and some of these documents are based on the existing formats of "La Constructora". Based on this diagnosis, it is identified that the methodological guide should contain twelve procedures which comply with the twenty-four processes of the PMBOK 5th edition, which includes the processes of the areas of integration, scope, time and cost, in addition to the process of identifying the stakeholders of the stakeholders area After developing the methodological guide, this applies to the construction phase of the project: residential complex of social interest housing "Parque Real" in Mosquera Cundinamarca, for the groups of initiation and planning processes, according to the procedures and formats carried out. On the one hand, the current shortcomings of project management are exposed and at the same time it shows that the guide is a tool that can improve and strengthen the management of "La Constructora" projects. This methodological guide is applicable to all the real estate developments of social interest made by "La Constructora", since it is aligned with the PMBOK 5th edition and the construction company can standardize its processes to similar projects within the company. The application of the guide allows the project manager to detect deviations in a timely manner in order to establish action plans to correct them and thus avoid losses in time and cost to the project. The development of the guide and the presentation of the results for the real park project, allows to consolidate the knowledge obtained during the development of the specialization and allows to make the necessary adjustments during the process to obtain the expected results. Lastly, the working group recommends that the guide be supplemented with the other process areas of the PMBOK 5th edition, which were not contemplated in this guide due to time limitation to develop the degree project.